EXTENSION AGRICULTURAL INNOVATION FOR BEE KEEPERS TO DEVELOP AND INCREASE PRODUCTIVITY IN THE CENTRAL REGION OF IRAQ - & AL – Bedrey, AL- Kafage (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The research aimed to identify the level of bee keepers innovation to develop and increase productivity in the central region of Iraq , In order to achieve the goals of research a questionnaire consisted of two parts, designed the first part included a bilateral scale to measure the level of beekeepers innovations, consists of ( 46 ) paragraphs Distributed on five fields (bee keeping , the area to take advantage of the bees in environment, the detection of diseases and pests ,the treating diseases and pest control , the field of honey products and peripherals manufacturing ), The second part included a barometer quadrilateral to measure the reasons consists of ( 34 ) paragraphs Distributed on four pivots (environmental causes , extension, economic , social). The research community a random sample ( 38%)of the  which is (Baghdad, Babil, Najaf) a random sample (15%) of the total number of beekeepers totaling (1098) breeders in the provinces covered by the research, to be the size of the sample (165) educator for the bees . The results showed  that bee keepers suffer from weak innovation levels, as the highest rate is (66.7%) of the beekeepers within the level of innovation (0-15) and an average of (11.12) degree and a standard deviation (7.53) degrees . The results showed that the causes that lead bee keepers to innovation is (social causes) came first in the level of importance as it reached the level of significance (2.38) degrees while last (extension causes) and the level of significance (1.93) degrees Researcher recommends the necessity of providing the requirements and production equipment for beekeeping encouraging high international standard prices in order to promote the level of innovation to beekeepers in central region of Iraq and should be concerted efforts by government agencies and of devices guidance, research and beekeepers.